Lnc-C/EBPβ Modulates Differentiation of MDSCs Through Downregulating IL4i1 With C/EBPβ LIP and WDR5 - Gao, Yunhuan; Shang, Wencong; Zhang, Dan; Zhang, Shiwu; Zhang, Xipeng; Zhang, Yuan; Yang, Rongcun (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs), which play an important role in tumor and inflammatory diseases, are divided into two subsets CD11b+Ly6ChiLy6G– monocytic MDSC (Mo-MDSC) and CD11b+Ly6Clow/negLy6G+ polymorphonuclear MDSC (PMN-MDSC) cells with different immunosuppressive function. However, it is poorly understood the mechanism(s) to control the differentiation of Mo-MDSCs and PMN-MDSCs. Here, we found that lnc-C/EBPβ may impede generation of Mo-MDSCs, but promote PMN-MDSC differentiation in vitro and in vivo. We demonstrated that lnc-C/EBPβ mediated differentiation of MDSCs was through downregulating multiple transcripts such as IL4il. Lnc-C/EBPβ not only bound to C/EBPβ isoform LIP to inhibit the activation of C/EBPβ but also interacted with WDR5 to interrupt the enrichment of H3K4me3 mark on the promoter region of IL4i1. Data also imply that the conserved homo lnc-C/EBPβ have a similar function with mouse lnc-C/EBPβ. Since MDSC subsets exert different suppressive function, lnc-C/EBPβ may be acted as a potential therapeutic target for inflammatory and tumor-associated diseases.